Pitfalls in the characterization of circulating and tissue‐resident human γδ T cells. Issue 6 (22nd January 2020) - Beucke, Nicola; Wesch, Daniela; Oberg, Hans‐Heinrich; Peters, Christian; Bochem, Jonas; Weide, Benjamin; Garbe, Claus; Pawelec, Graham; Sebens, Susanne; Röcken, Christoph; Hashimoto, Hisayoshi; Löffler, Markus W.; et al.
Abstract: Dissection of the role and function of human γδ T cells and their heterogeneous subsets in cancer, inflammation, and auto‐immune diseases is a growing and dynamic research field of increasing interest to the scientific community. Therefore, harmonization and standardization of techniques for the characterization of peripheral and tissue‐resident γδ T cells is crucial to facilitate comparability between published and emerging research. The application of commercially available reagents to classify γδ T cells, in particular the combination of multiple Abs, is not always trouble‐free, posing major demands on researchers entering this field. Occasionally, even entire γδ T cell subsets may remain undetected when certain Abs are combined in flow cytometric analysis with multicolor Ab panels, or might be lost during cell isolation procedures. Here, based on the recent literature and our own experience, we provide an overview of methods commonly employed for the phenotypic and functional characterization of human γδ T cells including advanced polychromatic flow cytometry, mass cytometry, immunohistochemistry, and magnetic cell isolation. We highlight potential pitfalls and discuss how to circumvent these obstacles. Abstract : Describes common methods used for characterizing the phenotypic and functional aspects of human γδ T cells; including potential pitfalls and ways to circumvent these obstacles.